From Model Transformation to Model Integration based on the Algebraic Approach to Triple Graph Grammars - Ehrig, Hartmut; Ehrig, Karsten; Hermann, Frank (Electronic Communications of the EASST, 2008)
Success and efficiency of software and system design fundamentally relies on its models. The more they are based on formal methods the more they can be automatically transformed to execution models and finally to implementation code. This paper presents model transformation and model integration as specific problem within bidirectional model transformation, which has shown to support various purposes, such as analysis, optimization, and code generation. The main purpose of model integration is to establish correspondence between various models, especially between source and target models. From the analysis point of view, model integration supports correctness checks of syntactical dependencies between different views and models. The overall concept is based on the algebraic approach to triple graph grammars, which are widely used for model transformation. The main result shows the close relationship between model transformation and model integration. For each model transformation sequence there is a unique model integration sequence and vice versa. This is demonstrated by a quasi-standard example for model transformation between class models and relational data base models.